AI and digital justice in EU labor law. A comparative study on predictive tools and judicial transformation - Molinari, Marianna; Giacalone, Marco (Frontiers in Artificial Intelligence, 2026)
This paper examines how artificial intelligence (AI) and digital tools are reshaping European labor law litigation, particularly in redundancy disputes. Conducted within the I-Tools To Design And Enhance Access To Justice (IDEA) project, it draws on a comparative survey across six Member States—Belgium, Croatia, the Czech Republic, Estonia, Italy, and Lithuania—to identify best practices in digitalized court systems. The findings point to uneven digital maturity: Estonia and Lithuania lead in digital development (8.4/10; 8.0/10) and show more favorable attitudes toward predictive justice (6.0/10; 5.8/10); whereas Belgium, Croatia, the Czech Republic, and Italy, despite having digital tools, struggle to integrate them into routine legal workflows, reinforcing greater resistance to predictive justice. Although digital justice can improve access and efficiency, concerns persist around fairness, judicial trust, and ethical safeguards. Progress, the study suggests, depends on participatory governance, clear regulation, and the careful integration of technology into procedural frameworks. Building on these insights, the current phase of IDEA positions AI as a regulatory instrument that structures access to justice and guides user behavior. The consortium is developing a legal chatbot to guide workers and employers toward the most suitable resolution pathway—negotiation, mediation, or litigation—based on context, cost, and procedural guarantees. The chatbot tailors its responses in accordance with prevailing legal trends and the reasoning behind case law. A pilot in three Member States (MSs) will test its potential to enhance transparency, empower users, and promote proportional, informed dispute resolution within European labor justice. Against this backdrop, the chapter conceptualizes AI—operating through structured information, triage, and explainability—as a regulatory instrument that can steer behavior ex ante and support compliance ex post in redundancy disputes, complementing adjudication without displacing judicial authority.